2022
DOI: 10.2147/opto.s337920
|View full text |Cite
|
Sign up to set email alerts
|

OSDI Outcomes Based on Patient Demographic and Wear Patterns in Prosthetic Replacement of the Ocular Surface Ecosystem

Abstract: Purpose: To evaluate the impact of prosthetic replacement of the ocular surface ecosystem (BostonSight PROSE) treatment on symptom outcomes based on the Ocular Surface Disease Index (OSDI). Patients and Methods: This was a single-center, retrospective analysis of consecutive patients who initiated PROSE treatment between September 2017 and December 2019 by the same clinician. The primary outcome measure was to compare OSDI survey scores at baseline prior to PROSE treatment and at follow-up, after PROSE treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Scleral devices have been demonstrated to improve and stabilize visual acuity in patients with limbal stem cell deficiency 6,7 and shown to support the function of the corneal epithelium. [8][9][10] Even so, there is limited literature describing scleral device use in patients with ectodermal dysplasia. 1 There are various reports in the literature about sightthreatening ocular complications of EEC syndrome where pharmacological agents alone did not seem to prevent disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scleral devices have been demonstrated to improve and stabilize visual acuity in patients with limbal stem cell deficiency 6,7 and shown to support the function of the corneal epithelium. [8][9][10] Even so, there is limited literature describing scleral device use in patients with ectodermal dysplasia. 1 There are various reports in the literature about sightthreatening ocular complications of EEC syndrome where pharmacological agents alone did not seem to prevent disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, scleral devices were not presented as a potential treatment option in any of these cases. Although each case is unique and scleral lenses may not be suitable for all EEC syndrome cases, the reported benefits of scleral lenses in LSCD 6,7,9 and the effect these lenses have on the support of the ocular surface, [6][7][8][9][10] presumably they may have potentially played a positive role in the patients/cases reported above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can improve vision in patients with complex corneal geometry. 18,19 They can serve as an effective treatment for PED, averaging complete healing at 8 days. 20 In addition, the use of a scleral lens as a drug delivery system has been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Our study's results are consistent with previous research that has examined the relationship between pre-existing symptoms and OSDI severity. For instance, Asghari et al (2022) [ 19 ] conducted a similar study and reported that patients with severe OSDI scores were more likely to have pre-existing symptoms compared to those with non-severe scores. This supports the notion that pre-existing symptoms play a role in the severity of OSDI scores, and our findings further highlight the impact of symptom worsening.…”
Section: Discussionmentioning
confidence: 99%